Male Athlete Representations in Men’s Magazines: A Study in Mediated Sport Stacking - Denham, Bryan E. (Communication & Sport, 2020)
This study examined 681 male athlete features in Details, Esquire, GQ, and Playboy across the first two decades of the 21st century. While White athletes accounted for 283 features and Black athletes 329, the former were featured in 35 of 43 sports observed, compared to just 14 for the latter. In fact, more than 80% of all features on Black athletes focused on basketball, football, and boxing. Latino athletes accounted for 52 of the 681 total features and represented 15 sports, one more than African Americans. Recognizing existing research, the study applies the term mediated sport stacking to the practice of limiting the Black athletic experience primarily to team sports, especially basketball. The article considers the implications of statistical patterns observed and also includes limitations and recommendations for future research.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMTY3NDc5NTE5ODM2NDQ5